PENYELESAIAN SENGKETA KEWENANGAN ANTAR PEMERINTAH DAERAH KABUPATEN KLATEN DENGAN PEMERINTAH KOTA SURAKARTA DALAM PEMANFAATAN SUMBER AIR COKRO KLATEN BERDASAR PERATURAN PERUNDANG-UNDANGAN - Husodo, Jadmiko Anom; Fatichadiasty, Fiqi (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
The regional autonomy, giving authority to each region to set and managing availablity of natural resources.Through cooperation between the regions optimization the utilization of natural resources especially water to the welfare of all indonesians can be achieved .But in the fact, conflict / dispute often occur between regions caused by differences in perception/ philosophy to the utilization of natural resources itself and carefulness of local government in assessing cooperation made to rules regulations that constantly changing dynamically. Like dispute authority that occur between the Klaten district government with Surakarta government city in water resources Cokro utilization in Klaten district.